The Application of Scanning Strategy in Teaching Students’ Reading Comprehension of Narrative Text - Cahya Komara; Sarah Marianda Dewi (Journal of English Language Teaching and Linguistics, 2021)
This research investigates the application of scanning strategy in teaching ninth-grade EFL students’ reading comprehension of narrative text. The aim is to know whether the use of scanning strategy gives tremendous effect to the ninth-grade students’ reading comprehension of narrative text or not. The researchers proposed scanning because it is potential and powerful strategy to lift students’ better narrative text reading understanding. To prove that, the quantitative method is used in this study by conducting quasi-experimental design which involved two classes of ninth-grade students at one private secondary school in Bekasi. The experimented class was around 34 students as well as the controlled class which was around 34 students. The researchers used pre-test and post-test reading narrative text instruments within 20 questions that were asked by the WH-question pattern to collect the data. After the data have been collected, the researchers fulfilled the standard pre-requisite analysis of Normality and Homogeneity before the hypothesis statistic test. At the end, the hypothesis statistic findings showed that tobserved was known by score 6.905 while ttable was obtained 1.996 in the level of 5% significance. Because of tobserved was higher than ttable, itcan be concluded that the application of scanning strategy is effective in teaching the ninth-grade students’ reading comprehension of narrative text at one private secondary school in Bekasi.